Canada's foreign policy : principles and priorities for the future : report ([Committee] [Ottawa]CA, 1994)
Examines the major issues, the Canadian interests involved and the options available. Makes recommendations for future policies to meet the new foreign policy agenda. Identifies the most important global requirements for the 90s and beyond as shared security, shared prosperity and shared custody of the environment.
DC